1993
DOI: 10.1080/01431169308954041
|View full text |Cite
|
Sign up to set email alerts
|

A GIS based methodology for small scale monitoring of tropical forests—a case study in Sumatra

Abstract: A Geographical Information System based methodology was developed in the framework of global survey of tropical vegetation using satellite data; it was tested on the forests of Sumatra with time series of NOAA AVHRR GAC and LAC data of 1982, 1988 and 1989. After some geometrical registration and radiometric optimization, these data are processed through a mono-date approach for minimizing the strong and highly variable atmospheric effects. Final results are derived from superimposing single-date classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…in the image classification process, and earlier studies have demonstrated the use of a DEM for a number of purposes [1]. DEM integration in image classification has helped increase the classification accuracy of digital data [7][8][9][10][11][12]. A DEM has also been used to describe the distribution of terrain components which contribute to spectral response [13], identify sites for fieldwork [14], geographically stratify training areas or homogeneous regions [17], and provide topographic normalization of Landsat TM digital imagery [16].…”
Section: Introductionmentioning
confidence: 99%
“…in the image classification process, and earlier studies have demonstrated the use of a DEM for a number of purposes [1]. DEM integration in image classification has helped increase the classification accuracy of digital data [7][8][9][10][11][12]. A DEM has also been used to describe the distribution of terrain components which contribute to spectral response [13], identify sites for fieldwork [14], geographically stratify training areas or homogeneous regions [17], and provide topographic normalization of Landsat TM digital imagery [16].…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing has been used to document and model changes in the extent and characteristics of forests (e.g. Skole and Tucker, 1993;Gastellu-Etchegorry et al, 1993), 16 wetlands (e.g. Sebastini et al, 1989), deserts, 17 different land use types (e.g.…”
Section: Threatened Areasmentioning
confidence: 99%
“…Given the volume of data to be analyzed, there is, however, a need for an automatic procedure providing an objective reliable vegetation classification adapted to the AVHRR resolution (Malingreau, 1992). The aim was therefore to investigate the potential of the AVHRR tool to carry out a forest/non-forest classification without a preliminary sampling stage (using thematic informations such as maps, field data) such as is used in a supervised classification process (Cross, 1990;Gastellu et al, 1993). The output classification produced from this work has to be based primarily on the satellite data providing the advantage of an easy continuous updating as new data are acquired.…”
Section: Classifyingmentioning
confidence: 99%